Mechanisms Regulating Protein Localization. (1st September 2015) - Bauer, Nicholas C.; Doetsch, Paul W.; Corbett, Anita H.
Abstract : Cellular functions are dictated by protein content and activity. There are numerous strategies to regulate proteins varying from modulating gene expression to post‐translational modifications. One commonly used mode of regulation in eukaryotes is targeted localization. By specifically redirecting the localization of a pool of existing protein, cells can achieve rapid changes in local protein function. Eukaryotic cells have evolved elegant targeting pathways to direct proteins to the appropriate cellular location or locations. Here, we provide a general overview of these localization pathways, with a focus on nuclear and mitochondrial transport, and present a survey of the evolutionarily conserved regulatory strategies identified thus far. We end with a description of several specific examples of proteins that exploit localization as an important mode of regulation. Abstract : One rapid and efficient mechanism for regulation of protein function is targeted localization. Moving an active protein into a target compartment avoids the expensive need for new protein synthesis. Furthermore, this mode of regulation is rapidly reversible. This review provides an overview of intracellular targeting pathways and then presents mechanisms by which regulation of localization is achieved. Pathways covered in detail include nucleocytoplasmic and mitochondrial transport with more general overviews of chloroplast, peroxisomal, ciliary, endomembrane and vesicular transport.